Visio Vox SIP videophone system on LAN - Ignacio, Michael Q.
Desktop videophones have cut travel costs and improved productivity of several large companies. Because of this, it was predicted that the market for desktop videophones will continue to grow in the coming years. The success of new products, however, has become highly dependent on users' experience in using the products. With this, the problem with the most of the commercially available videophones is that they are cumbersome and difficult to use. In addition, their video displays are too small and resolutions are low as well. The objective of this project was to develop the videophone application of a desktop videophone system ? VisioVox - that has an acceptable user Quality of Experience (QoE) by providing high-resolution video and a user-friendly interface. We implemented the system over a Local Area Network (LAN) using the Session Initiation Protocol (SIP) standard. VisioVox was built initially on an All-in-One PC (AIOPC) system with a widescreen display, combined with a high-resolution camera with built-in microphone. We used free and open source software (FOSS) to develop the videophone application that was composed of video telephony functions and the user interface (UI). The resulting videophone application can deliver video at a higher 704 x 576 pixels (4CIF) resolution compared with existing videophones, and at least 15 frames per second (fps) frame rate. Since the project's primary focus was the development of bas software and design of effective and compelling videophone UI, we, therefore, evaluated the QoE of the videophone application alone. Specific QoE parameters such as communication end-to-end delay, overall audiovisual quality, and usability were assessed using both objective and subjective methods. In all of these metrics, VisioVox's QuO was found to be within the acceptable value. For future project phases, VisiVox is intended to be developed as an integrated touchscreen embedded product to create a manageable desktop videoconferencing solution, using the software developed in this project.